The Effect of Service Recovery on Customer Satisfaction with Customer Trust as an Intervening Variable - Chrisdwiandra, Imadji (LifeSciFi, 2024)
In today's competitive business world, customer satisfaction is one of the main focuses of companies in maintaining their reputation and growth. However, in the midst of efforts to meet customer expectations, things do not always go according to plan. Sometimes, errors or customer dissatisfaction occur in the service process or business transactions. This is what encourages researchers to consider the importance of service recovery in the EV Charging division of PT PLN Haleyora Power Jateng DIY, as an effort to restore customer satisfaction after dissatisfaction or detrimental incidents. Service recovery is a strategy that focuses on how companies respond to and resolve customer complaints or dissatisfaction. However, the success of service recovery is determined not only by how well the company resolves the problem, but also by how those efforts affect the customer's perception of the company as a whole. Therefore, the role of customer trust as an intervening variable is very important in understanding the relationship between service recovery and customer satisfaction. This research uses explanatory research methods with quantitative methods. Explanatory research is research with the aim of finding out whether there is a relationship and influence between the independent variables and the dependent variable. If there is a relationship and influence, then how close is the relationship and influence to the Partial Least Square (PLS) test tool? The research results show the importance of customer trust as an intervening variable in the relationship between service recovery and customer satisfaction because trust plays an important role in moderating customer perceptions of recovery efforts carried out by the company.